Internet policy and regulation through a socio-cultural lens - Tsatsou, Panayiota (Javnost (Ljubljana), 2010)
This article argues that a dialogue of society and its culture with decision-making practices is taking place in the information society and with respect to phenomena such as digital divides. The article reports on focus group research conducted in Greece. This qualitative research concerns Internet policy and regulation in particular and examines the dialogue of policy and regulation with societyćs culture as reported by users and non-users of the Internet. The research finds that the perceived role of Internet policy and regulation passes through societyćs everyday culture, with significant implications for the implementation, efficiency and future course of Internet policy and regulation. These findings aim to fill in the relevant gap in the literature which often neglects the interlinkages between society's cultural traits and mindsets and the practices applied in the complex field of policy and regulation for the information society.
Keywords: communication; komuniciranje; elektronski mediji; internet; politični vplivi; regulacija; Grčija; Greece